The rational and long term use of pedigree cocks in the selection of hen of egg direction productivity - Васильєва, О. О. (Scientific Progress & Innovations, 2012)
The problem of expedience and efficiency of the use of two- and three-year cocks in the selection of bird of egg direction productivity with cell technology of maintenance and in the system of artificial insemination has been researched. Sperm quality of cocks does not change with the age, reproductive capabilities of old cocks and indices of incubation qualities of eggs at the use them in the system of artificial insemination are not diminished. Egg productivity of daughters, got from the cocks of the first year, substantially lower, than from daughters, got from 2–3-years-old cocks. It is recommended to use old cocks very limitedly and, mainly, on groups of multipliers of clean lines for an increasing desirable genotypes in the flock. Cocks in age of 2–3 years are fully estimated on genetic and reproductive parameters and their use in breeding of egg bird increases the selection effect.